A prospective study of gestational trophoblastic disease profile with special reference to mortality and pregnancy outcome after successful management of the same - Bhattacharya, Abantika; Panja, Tanmay Kanti; Bhattacharya, Amiya; Baur, Baijayanti; Madhwani, Kishore P. (International Journal Of Community Medicine And Public Health, 2019)
Background: Gestational trophoblastic disease (GTD) is a group of rare tumors that involve abnormal growth of cells inside a woman’s uterus. GTD does not develop from cells of the uterus like cervical cancer or endometrial (uterine lining) cancer do. Instead, these tumors start in the cells that would normally develop into the placenta during pregnancy. GTD is unique because the maternal lesions arise from the fetal tissue as a molar pregnancy. All forms of GTD can be treated. In most cases the treatment produces a complete cure. The study was conducted to assess the various presenting features of GTD and factors associated with it. Methods: It was an observational hospital based prospective epidemiological study. Complete enumeration technique was followed and a total of 305 female patients were included in the sample. A pre-designed and pre-tested interview schedule was used to record different information and detailed history. Results: Of the 305 patients studied, 67.2% were diagnosed with H. mole, 23% patients were diagnosed with gestational trophoblastic tumor, among them 4.9% had choriocarcinoma. Majority were primigravida and of blood group O type. Pregnancy outcome after successful management of GTD were 63.3% had full term pregnancy, 20% cases had repeat molar pregnancy, 10% had spontaneous abortion while 6.7% (2/30) had pre term delivery. Conclusions: Gestational trophoblastic disease is seen most commonly in reproductive age group. If it is not diagnosed on time it can be fatal. This is a highly curable tumor even in the presence of distant metastasis.